Biodegrability Analysis Of Banana Stem Fiber And Polyethlene Terephthalate (PET) Polymer Composite As A Substitute For Styrofoam: Analisis Uji Biodegrabilitas Komposit Serat Batang Pisang Dan Polimer Polyethlene Terephthalate (PET) Sebagai Pengganti Styrofoam - Rahma Ayu Syafitri; Tri Widayatno (Jurnal Kimia dan Rekayasa, 2026)
This study aims to examine the potential of banana stem fiber and polyethylene terephthalate (PET)-based composites as biodegradable materials to replace styrofoam. Banana stem fibers are used as natural reinforcement materials combined with PET and PLA resin, with variations in fiber length (2 cm and 6 cm) and composition ratios (10:90, 40:60, 55:45, and 70:30). The composite manufacturing process was carried out using the hand lay-up method, then tested through biodegradability tests, tensile tests, and electron microscopy (SEM) characterization. The results of the biodegradability test showed that the composite variation with a ratio of 10:90 and a fiber size of 6 cm had the highest degradation rate of 11.81%. In the tensile test, the highest strength value was recorded at 13.16 MPa in the same variation. The results of the strain and elastic modulus tests also showed that the composition and size of the fibers affected the mechanical properties of the composite. Meanwhile, the results of SEM characterization showed varying interactions between the fibers and the matrix. These results demonstrate that the banana stem fiber and PET composite has the potential to be an environmentally friendly alternative packaging material, demonstrating mechanical properties and biodegradability that support its application as a replacement for Styrofoam. AbstrakPenelitian ini bertujuan untuk mengkaji potensi komposit berbasis serat batang pisang dan polyethylene terephthalate (PET) sebagai material biodegradable pengganti styrofoam. Serat batang pisang digunakan sebagai bahan penguat alami yang dikombinasikan dengan PET dan resin PLA, dengan variasi panjang serat (2 cm dan 6 cm) serta rasio komposisi (10:90, 40:60, 55:45, dan 70:30). Proses pembuatan komposit dilakukan menggunakan metode hand lay-up, kemudian diuji melalui uji biodegrabilitas, uji tarik, dan karakterisasi mikroskop elektron (SEM). Hasil pengujian biodegrabilitas menunjukkan bahwa variasi komposit dengan rasio 10:90 dan ukuran serat 6 cm memiliki laju degradasi tertinggi sebesar 11,81%. Pada uji tarik, nilai kekuatan tertinggi tercatat sebesar 13,16 MPa pada variasi yang sama. Hasil uji regangan dan modulus elastisitas juga menunjukkan bahwa komposisi dan ukuran serat berpengaruh terhadap sifat mekanik komposit. Sementara itu, hasil karakterisasi SEM memperlihatkan interaksi yang bervariasi antara serat dan matriks. Dengan hasil tersebut, komposit serat batang pisang dan PET memiliki potensi sebagai alternatif bahan pengemas yang ramah lingkungan serta menunjukkan sifat mekanik dan biodegrabilitas yang mendukung aplikasinya sebagai pengganti styrofoam.